الاحتكام إلى الأدلة القرآنية في ترجيح مسائل أصول الدين كتاب "الحق الدامغ" لأحمد حمد الخليلي أنموذجا - حباسي, خالد (University of Eloued جامعة الوادي, 2019)
امتاز الإباضية في مباحث العقيدة وطريقتهم في فهم أصول الدين بأشياء ثلاثة تميزت بأنها قرآنية استمدادا واستنادا، وهذا حسبما يوضحه المفتي العام لسلطنة عمان الشيخ أحمد الخليلي في كتابه"الحق الدامغ" وهي: 1- سلامة المنزع: الاستدلال على صحة المعتقد بين صحيح النقل وصريح العقل... 2- عدم التعصب لأئمتهم 3- المرونة والتسامح في معاملة سائر فرق الأمة. Ibadi excellence in the doctrine of the faith and their way of understanding the origins of religion by three things characterized as Koranic derived and based, and this, as explained by the Grand Mufti of the Sultanate of Oman, Sheikh Ahmed Khalili in his book, "the right of proof", namely: 1- Safety of Disqualification: Deducing the validity of belief between true transportation and explicit mind. 2 - non-intolerance to their imams 3 - flexibility and tolerance in the treatment of other teams of the nation.
: الدور العُماني في خدمة القرآن الكريم وعلومه المعهد العالمي لوحدة المسلمين بالجامعة الإسلامية العالمية بماليزيا تاريخ انعقاد الملتقى:2-3/10/2019 كوالالمبور- ماليزيا
Keywords: الأدلة القرآنية ، أحمد الخليلي،، أصول الدين، التعصب، مرتكب الكبيرة، تخليد الفساق في النار; the Qur'anic evidence, Ahmed al-Khalili, the fundamentals of religion, intolerance, the perpetrator to ward off large, immortalized in the fire